Physically based optical parameter database obtained from real materials for real-time material rendering. (October 2018) - Hong, Sungin; Lee, Chulhee; Chin, Seongah
Abstract: In order to render objects in computer graphics and video games that closely resemble real objects, it is necessary to emulate the physical characteristics of the material and determine optical parameters consisting of an absorption coefficient and a scattering coefficient, which are measured from real objects. In this study, we propose a physically based rendering technique that enables real-time rendering by extracting the optical parameters required for rendering opaque and translucent materials and then collecting the obtained information in a database (DB). For this purpose, optical parameters were extracted from the high-dynamic-range image (HDRI) of an object, which was obtained using self-produced optical imaging equipment by taking images of its upper and lower parts. Furthermore, by binding the optical parameter with the texture of the corresponding material, 122 material-rendering DB sets were established. The validity of the proposed method was verified through the evaluation of the result by 118 users.